Удосконалення технологій молоковмісних продуктів шляхом використання харчових емульсій - Устименко, Ігор Миколайович (My University, 2019)
У дисертаційній роботі аналітично та експериментально обґрунтовано удосконалення технологій окремих видів молоковмісних продуктів шляхом використання нормалізаційних харчових емульсій різного хімічного складу. На підставі теоретичних і експериментальних досліджень розроблено технології емульсій з масовою часткою жиру від 30 до 50 %. Доведено застосування емульсій в технологіях білково-жирових, сметанного продуктів та морозива з комбінованим складом сировини. Встановлено, що органолептичні, фізико-хімічні та мікробіологічні показники повністю відповідають нормативним вимогам аналогів цих продуктів. Розроблено параметричні та апаратурно-технологічні схеми виробництва нових видів молоковмісних продуктів. Практична значимість розробленої технології полягає у виключенні необхідності проведення гомогенізації всього об'єму молоковмісних сумішей та забезпечення стабільності показників якості готової продукції. Розроблені молоковісні продукти, у порівнянні з їхніми аналогами, мають підвищенну харчову цінність. In the dissertation the expediency of application of vegetable oils, products of their processing and emulsifiers of various origin in the composition of direct-type food emulsions with a mass fraction of fat from 30 to 50% as normalization components in technologies of new types of milk-containing products - analogues of cottage cheese, sour cream and ice cream. A synergistic interaction between selected emulsifiers of different nature is established, which allows to obtain a stable and fine dispersed food emulsion. According to the results of the analysis physico-chemical parameters of emulsions, the composition of the emulsifying complex consisting oleophilic and hydrophilic emulsifiers domestic production (emulsifier of the brand "Tverdiy - 2 (T-2)" + sodium caseinate is optimized). The rational content of the emulsifying complex in the composition of food emulsions with a mass fraction of fat 30, 40 and 50% in the amount of 1,55 ... 4,55% is established. For the first time the laws of changing the temperature melting of fats on the content of high melting oleophilic emulsifiers Esther P, Tverdiy - 2 (T-2), Esther P 02 and Esther P 020 in the range from 0,5 to 1,5%, which allows to predict the flow the process of crystallization triglycerides and the temperature regimes of the emulsification process. Correlation interrelation between the melting point of the fat phase emulsion with an upper limit of 35 °C and homogenizing temperature in the range from 55 °C to 70 °C is established, which is determined by the dependence of the effectiveness emulsification on the viscosity characteristics fatty phase. Scientifically grounded technological modes of homogenization of emulsions. For the first time mathematical models of optimization of the composition of food emulsions with different fat content, describing the laws of the influence emulsifying complex on the dispersion the fat phase, and can predict the effectiveness emulsification process in production conditions. It was established that the use in the composition of food emulsions of a complex emulsifiers of different nature allows them to achieve their highest stability for the size of fat balls not exceeding 2 microns. According to the results of microbiological studies of food emulsions, it was established that the NMAFAnM of all samples immediately after receiving the emulsion is at the level (1.6 ... 4.8) • 102 CFU/g and three orders of magnitude lower than the regulatory requirements (NMAFAnM, CFU/g, not more than 2 105). In addition, in the samples tested, E. coli bacteria was not detected in 0.01 g, and the number of spores of mold fungi and yeast was less than 30 CFU/g. Consequently, the temperature regimes of pasteurization and homogenization of emulsions completely provide the microbiological purity food emulsions and allow them to temporarily store them for 2 days at a temperature of 4...6 ° C. As part of a new type paste cottage cheese product with a fat content of 2 to 18 %, it is suggested to use a food emulsion with a mass fraction of fat 50 % on the basis of "Violia-molzhir 3" life-cycle or a food emulsion based on sunflower oil and linseed oil. Milk-protein granular product with a fat content of 4 to 6 % was obtained using a food emulsion based on blended oil (sunflower oil + linseed oil) with a mass fraction of fat 30 %, which allowed enriching it with polyunsaturated fatty acids. The product of sour cream with a fat content of 10 to 20 % was obtained using an emulsion based on «Violia-molzhir 3» with a mass fraction of fat from 30 to 50%. Ice cream with a combined composition of raw materials from fat 3.5 to 15% were obtained using a mixture of food emulsions based on the milk fat substitute and 40% fatty oil («Violia molzhir 3» + corn oil), ("Violia molzhir 3" + (sunflower oil + oliveoil)). The bulk of oil from the total fat content is 15-25% to provide the recommended product for this product resistance to dying (not less than 43 min) and loss (not less than 60%). It was established that the organoleptic, physico-chemical and microbiological parameters of new types milk-containing products fully meet the regulatory requirements of their analogues, manufactured according to the classical technology. New types of milk-based foods with the use of food emulsions can be considered as a source of saturated and monounsaturated fatty acids, since their degree of availability from the daily norm is more than 5 %. The degree of satisfaction of the daily norm in polyunsaturated fatty acids in these types of milk-containing products is satisfactory, since it ranges from 0,5 to 2,5 g per 100 g of product. The calculation of the expected technical and economic effect from the introduction of scientific development is carried out. Implementation of scientific research results can reduce the cost and increase the profitability of the developed types milk-containing products. The social significance of the development results lies in: development of technology of cottage cheese, milk-protein granular, sour cream products and ice cream with a combined composition of raw materials; nutritional value due to enrichment with polyunsaturated fatty acids and in the absence fatty trans-isomers; expansion of the range of milk-containing products that meet the modern requirements of the concept healthy food; providing the population of the country with biologically-complete products at affordable prices.
Keywords: емульгатори; комплекси емульгаторів; казеїнат натрію; харчова емульсія; технологія; молоковмісні продукти; emulsifiers; complexes of emulsifiers; sodium caseinate; food emulsion; technology; milk-containing products; кафедра технології молока і молочних продуктів